Selling the CIA public relations and the culture of secrecy - McCarthy, David Shaumus (University Press of Kansas, 2018)
"In Selling the CIA, David McCarthy contends that events that unfolded during the 1970s badly damaged the CIA's mystique, which had been assiduously cultivated since the Agency's inception in 1947. In response to the unprecedented crisis, CIA officials developed a far-reaching public relations strategy. McCarthy's is the first systematic history of CIA public relations between 1974 and 2014, demonstrating that the culture of secrecy at the CIA and its PR campaigns are fundamentally intertwined"...
Includes bibliographical references and index
Keywords: United States -- Central Intelligence Agency -- History; USA -- Central Intelligence Agency; Geschichte 1973-2017; HISTORY / United States / 20th Century / bisacsh; POLITICAL SCIENCE / Political Freedom & Security / Intelligence / bisacsh; Intelligence service -- United States -- History; Public relations -- United States -- History; HISTORY / United States / 20th Century; POLITICAL SCIENCE / Political Freedom & Security / Intelligence